A Comparative Study On The Psychosocial Adjustment Level Between Elderly Practitioners And Non-Practitioners Of Physical Activity - العربي بن كحلة; مويسي فريد (Journal of Sport Science Technology and Physical Activities, 2021)
The study aims to compare the level of psychosocial adjustment between elderly practitioners and non-practitioners of physical activity. For this purpose, we used a descriptive research method on a deliberately sample composed of (70) elderly practitioners and non-practitioners over age (65). For data collection, we used Elderly's Psychosocial Adjustment Scale by Abdel Hamid El-Shazly (2001). After collecting the results and having treated them statistically, we conclude that the level of psychosocial adjustment among the elderly practitioners is higher than the non-practitioners of physical activity. On this basis, the study recommended community’s role in supporting and encouraging older adults to practice physical activity, as well as media advocacy in promoting sports and physical activity.